Ultrasonic Coal-Wash for De-Ashing and De-Sulfurization Experimental Investigation and Mechanistic Modeling - Ambedkar, B.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This study focuses on the physical aspects of ultrasonic de-ashing and de-sulfurization, such as cavitation, streaming and their combined effects. Ambedkar Balraj proposes an ultrasound-assisted coal particle breakage mechanism and explores aqueous and solvent-based ultrasonic techniques for de-ashing and de-sulfurization. Ambedkar designs a Taguchi L-27 fractional-factorial matrix to assess the individual effects of key process variables. In this volume he also describes process optimization and scale-up strategies. The author provides a mechanism-based model for ultrasonic reagent-based coal de-sulfurization, proposes a flow diagram for ultrasonic methods of high-throughput coal-wash and discusses the benefits of ultrasonic coal-wash. Coal will continue to be a major fuel source for the foreseeable future and this study helps improve its use by minimising ash and sulfur impurities.
Literature review -- Assessment of fly-ash erosion potential of indian coals -- Experimental studies on ultrasonic coal beneficiation -- Experimental studies and mechanistic modeling of reagent-based ultrasonic coal de-sulfurization -- Assessment of benefits from ultrasonic coal-wash (uscw) -- Summary, conclusions and recommendations.
Keywords: Chemistry; Chemistry, Physical organic; Chemical engineering; Acoustics in engineering; Chemistry; Industrial Chemistry/Chemical Engineering; Physical Chemistry; Engineering Acoustics